Structural and Functional Insights into Riboflavin-Binding Proteins in Whooping crane (Grus americana) and Other Avian Species: An In silico Approach - Paramkusham, Srinivas; Mamidala, Estari; J. Madhukar, J. Madhukar (Journal of Neonatal Surgery, 2025)
Riboflavin-binding proteins (RfBPs) play a critical role in the transport and regulation of vitamin B2 across avian species. In this study, we conducted an in silico analysis of the physicochemical properties, amino acid composition, and secondary structure of RfBP in Grus americana (Whooping crane) and other bird species. Protein sequences were retrieved from the UniProtKB/Swiss-Prot database, and various physicochemical parameters were calculated using the ExPASy ProtParam tool. The amino acid composition was analyzed to compare RfBP sequences, and the secondary structure was predicted using the SOPMA tool to identify structural differences across species. The results revealed that the molecular weight of RfBP in Grus americana was higher compared to other species, with significant differences in isoelectric points, indicating diverse charge distributions. Amino acid composition showed a high percentage of conserved residues, such as serine and cysteine, suggesting their importance in protein structure and function. Secondary structure analysis indicated that alpha helices and random coils were the dominant structures across species, with minor variations in beta turns and extended strands, reflecting structural adaptations. In conclusion, this in silico analysis provides valuable insights into the structural and functional diversity of RfBPs in avian species, highlighting potential evolutionary adaptations and species-specific roles in riboflavin transport